RELIGIOUS ETHICS AND DIGITAL FAIRNESS: THEOLOGICAL REFLECTIONS ON ANTI-UNFAIR COMPETITION LAW AND ONLINE ADVERTISING BLOCKING - Lu, Xinhe (European journal for philosophy of religion, 2025)
The rise of unfair competition in the digital marketplace presents profound ethical and philosophical challenges, particularly in light of religious perspectives on justice, fairness, and economic morality. In an era defined by rapid technological advancement, digitalization, and artificial intelligence, traditional business ethics and market regulations face unprecedented transformations. While the expansion of Internet technology has facilitated economic growth and improved human life, it has also introduced new forms of competitive behavior that raise ethical concerns regarding fairness, transparency, and the protection of public interest. The practice of online advertising blocking, in particular, exemplifies a complex intersection of business ethics, legal frameworks, and digital rights, where determining the moral and legal legitimacy of such actions remains highly contested. This study explores online advertising blocking from the perspective of religious ethics and philosophical jurisprudence, integrating principles of justice, moral economy, and ethical responsibility found in religious traditions. It examines how religious doctrines on economic justice—such as Christian, Islamic, and Confucian perspectives on fair trade and commercial morality—can provide insights into the regulation of digital competition. Using the framework of the Anti-Unfair Competition Law of the People's Republic of China, this study assesses the legitimacy of advertising blocking practices, analyzing disputes from both theoretical and practical viewpoints. Given the rapid evolution of Internet markets, existing legal mechanisms struggle to address the fluid nature of digital competition, necessitating a reconsideration of regulatory strategies through an ethical and religious lens. By synthesizing legal, philosophical, and theological perspectives, this research proposes a more holistic approach to defining fairness in digital markets, emphasizing the role of ethical responsibility, human dignity, and moral regulation in shaping the future of online commerce. Future research should further explore the role of religious ethics in guiding digital governance and economic justice in the age of artificial intelligence and algorithmic decision-making.